Drama and the politics of generational conflict in Shakespeare's England - Gearhart, Stephannie S. (Routledge, 2018)
Introduction: historicizing generational conflict – Youth. Blood v. manners: youth's quest for independence in The merchant of Venice – Familial contracts: financial inheritance in the plays of Jonson and Middleton – Elders.
Literaturangaben
Keywords: Shakespeare; William; Conflict of generations in literature; Youth in literature; Old age in literature